The Relevance of Hudud and Ta'zir in Corruption Law Enforcement through the Perspective of Islamic Criminal Law - Angga Fadzar; Azmi Syakira; Khotijah Khotijah; Rere Citra Ramadhan; Firman Robiansyah (Fakultas Syariah Universitas Islam Negeri Sultanah Nahrasiyah Lhokseumawe, 2025)
Corruption is a serious crime that has a widespread impact on the state and society. However, law enforcement efforts still face various structural and implementation obstacles, such as weak deterrent effects, political intervention, and inconsistent court decisions. This study aims to explore the relationship between the concepts of hudud and ta'zir in Islamic criminal law and efforts to combat corruption within the framework of modern law. The research method used is qualitative through literature review, examining classical fiqh texts, national legislation, and relevant scientific literature. The results of the study indicate that corruption does not fall under the category of hudud because it does not meet the technical and substantive requirements determined by sharia. However, corruption can be classified as a ta'zir crime, which gives judges or authorities the flexibility to impose penalties based on the severity of the crime, ranging from fines, asset recovery, removal from office, to the death penalty in cases that cause widespread harm to the state. Compared to Indonesia's positive legal system, which tends to be weak in enforcing strict sanctions, the principles of ta'zir are considered more responsive and adaptive. Therefore, this finding recommends that the principles of ta'zir be used as a normative and philosophical reference in the formulation of national legal policies to create a more fair, strict, and socially just system for enforcing anti-corruption laws.